Um roteiro para criação de conteúdo digital baseado na metodologia de resolução de problemas - Relly, Alisson Rogério (2019)
The process of teaching and learning mathematics is surrounded by several difficulties that, if not overcome, end up accumulating knowledge gaps. These gaps in turn amplify the difficulties and end up harming the learning of new knowledge. The use of technology in teaching is a way to combat these difficulties, but for this are recommended software and applications with specific content and qualities that exploit the technological resources available, especially the resources present in mobile equipment such as smartphones, which has become increasingly popular. Although there are several software for teaching mathematics, technology is constantly evolving and it is necessary that technological resources for education also evolve generating the need to create new software. For the production of these softwares and applications there are several resources and scripts from software engineering, or even intuitive resources that do not require programming language knowledge, but for the production of content, no scripts and methodologies have been identified that can guide this step. Thus, this work, besides presenting a brief research on the use of technology in education, propose a roadmap for creating content for software and applications based on questions and answers. To make feasible the elaboration of the script, the characteristics of the SUAV application, under development at UFSM, were taken as reference. However, the roadmap can be applied to the development of any application or software that has similar characteristics. Because it is a question and answer application, the problem-solving methodology was used to base the script. At the end of the paper, some examples of content related to high school, created from the elaborated script, are presented.